SURVEY KETERAMPILAN DAN UJI VALIDITAS DRIBBLE DAN LAY-UP BOLA BASKET MAHASISWA PENDIDIKAN OLAHRAGA STKIP PGRI BANGKALAN - Abdillah Hidayat, Rifky; Hidayatullah, Fajar; Mukti Widodo, Haryo; Putri Purwoto, Septyaningrum (JURNAL ILMU KEOLAHRAGAAN, 2024)
Basketball is a team sport that is popular with many people, because it is not only healthy but also fun. The ability to master basic basketball techniques is necessary to create good cooperation between teams. The aim of this research is to determine the capacity of basic basketball dribbling and lay-up techniques among students of the 2022 Sports Education Study Program at STKIP PGRI Bangkalan. This research method uses test and measurement techniques. The results of this research are that the dribble and lay-up test instruments have a high level of validity with calculation results using the CVR formula of 1.00. Meanwhile, the instrument test results obtained an R2 of 0.562, which means it has moderate reliability. This research conducted a validity test on basketball dribbles using CVR validity to obtain a correlation coefficient of 0.733 or it could be stated to have high validity. Results of instrument testing in this study showed that the minimum value of the dribble instrument was 1.00, the maximum value was 3, the sum value was 69.00, the average value was 1.9714 and the standard deviation value was 0.45. The descriptive analysis of lay-up test results has a minimum value of 2.00, a maximum value of 4.00, a sum value of 82.00, an average value of 2.3429 and a standard deviation value of 0.59. The recommendation that will be given is the need for regular independent training for students using dribble and lay-up exercises to improve skills in the game of basketball